Examples from US Policies to Reduce Oversupply and Overutilization: Lessons for the Japanese Health Care System - Jared Lane K. Maeda PhD, MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The Japanese health care system provides universal coverage with relatively low cost sharing and patients have a free choice of providers. Although Japan’s government price controls have helped to restrain the growth in health care spending, the country’s rapidly growing elderly population and adoption of new drugs and technologies have placed increased fiscal pressures on its health care system. Additionally, the Japanese health care system does not have the infrastructure in place to restrain utilization, which may be a key driver of increases in health care spending. Although the US health care system has many shortcomings, such as the highest health care prices among developed countries and a significant uninsured population, it has been able to manage utilization by using various tools, such as prior authorization and gatekeeping. The US health care system might be able to offer Japan some lessons on ways to reduce unnecessary utilization and supply to create greater value in its health care system.